Introduzione - Piludu, Vesa; Frog, Etunimetön (2022)
New version (2021) of the Italian introduction (Piludu & Frog) previously published in 2014 (bilingual edition of the book - Italian and English) and in 2015 (Italian edition): the original Italian text has been reviewed, standardized and corrected, and there are new footnotes written for the Italian readers by the reviewers of the mythological series "Bifröst" (VociFuoriScena): Dario Giansanti and Elisa Zanchetta. The chapters are based on the papers of the scientific symposium: "Kalevala: Epica, Magia, Arte e Musica / Kalevala: Epic, Magic, Art and Music" organized in Bottenicco di Moimacco / Cividale del Friuli (Udine, Italy) for the centenary of Kalevalaseura (2011). Non peer reviewed